Extreme Solution: Menggugat Sistem Moneter (Fiat Currency) Menuntut Keadilan Kemanusiaan: Extreme Solution: Challenging The Monetary System (Fiat Currency) Demands Humanitarian Justice - -, Saiddaeni (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2024)
The problem from the 16th century until now was about a very stupid human invention, namely turning checks or bonds into money. Where this check has no intrinsic value in each piece. Even though humans have made very big discoveries using gold and silver coins with standard sizes for transactions. For this reason, this article was written to provide a solution to a monetary system that uses FIATCurrency which is unfair and violates human rights by stealing other people's wealth as the amount of money created increases. Where everyone must get justice and security in terms of the assets they own. This systematic theft must be resolved as soon as possible. This research method is a literature review using primary and secondary sources. The research results show that FIAT's solution to the dangers has been proven to be unjust to humans and detrimental to many people and even countries. The solution is to return to the Barter system. bartering can be a more equitable and sustainable measure for humanity, avoiding dependency and inflation on 'unique pieces of paper' that lose their value over time and restoring more basic values ​​related to life and natural resources.